Studi Efek Pemberian Probiotik Multistrain terhadap Parameter Klinis Diabetes Melitus: Review Sistematik - Mefri Widya Ningrum; Tjie Kok (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
ABSTRACT The purpose of this study was to analyze the study of the effects of multistrain probiotics on clinical parameters in diabetes mellitus to determine the condition of blood glucose and HbA1c so as to trigger inflammation. The research method uses a systematic review with the online scientific database Google Scholar, PubMed, Researchgate according to the inclusion and exclusion criteria. The results of this systematic review showed that 13 articles that had been extracted discussed the effects of giving probiotics as an alternative secondary treatment for complications of diabetes mellitus and 5 articles that were in accordance with the research objectives. From the results of a systematic review, it was concluded that probiotic treatment can reduce the level of resistance to HbA1c, GDP, GD2P and inflammatory mediator parts of diabetes mellitus. Keywords: Diabetes mellitus, HbA1c, Probiotics, Proinflammation